(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2021)
In this text, contributing with a possible inspiration for the didactics of Hispanic studies in the world, I present a form of work that we are accomplishing in the countryside of Brazil, in a city called Tangará da Serra, located in the State of Mato Grosso – a border state with Bolivia. As we have previously studied (Krauss 2016) the literary-editorial work carried out by the Cartonera Publishers – collectives that manufacture books with cardboard covers and that have gained more and more literary expression in Latin America – we understand that their catalog is a privileged gateway for a linguistic and literary work that strives to be counter-hegemonic (Palmeiro 2010, Navarro 2020). For this reason, I contacted a Bolivian Cartonera Publisher and proposed to coordinate a group of students willing to translate some of their titles for later publication in Brazil. When I realized that the students were engaged in the translation process, but did not relate much to each other, I made a proposal of a work of collective reading of the works that are being translated. Therefore, we meet weekly on the Google Meet platform to talk about the work we are reading. From an interpretative analysis of the meetings themselves and also from individual interviews conducted with all student-translators, I notice that this is a sort of dynamic that has produced positive effects for the relationship that Spanish-speaking students establish so much with the Spanish language and its literature, but, above all, that this is a circuit of work that has contributed to the deconstruction of a certain imaginary that surrounds our Bolivian neighbors disparagingly. Thus, from this data, we concluded that this is a practice which has helped a lot for the improvement of the word reading that offers itself as a support to improve the reading of the world of the students.